Guiding evidence-based classification in para sporting populations: a systematic review of impairment measures and activity limitations - Wileman, T. M.; McKay, M. J.; Hackett, D. A.; Watson, T. J.; Fleeton, J.; Fornusek, C. (Sports Medicine, 2025)
Background: As the focus of classification shifts towards an evidence-based approach, it is crucial to establish a robust system that relies on valid and reliable measures of impairment to ensure legitimate and competitive opportunities for all Para athletes. However, the lack of methods that possess the necessary measurement properties for assessing impairments in Para sporting populations presents significant challenges to developing an evidence-based classification system. Objective: This review aimed to identify and evaluate measures of impairment and activity limitation measures that have been used to assess eligible impairments in Para sport athletes for potential use in evidence-based classification. Methods: Six electronic databases (MEDLINE, Embase, SPORTDiscus, CINAHL, Scopus, Web of Science) were searched from their earliest record to December 2023. Results: Fifty-one articles were identified, with twenty-one studies focusing on physical impairment measures. Isometric and grip strength emerged as effective measures. Coordination measures, such as tapping tasks, showed variations with performance. Additionally, six studies focused on intellectual impairments, revealing differences between impaired and non-impaired athletes through generic cognitive tests. Vision impairment measures, including visual acuity and visual field assessments, displayed varying associations with performance across sports. Conclusions: Although research on evidence-based classification in Para sport is limited, this review provides valuable insights for sports in developing a testing battery that adheres to evidence-based protocols. Ongoing research efforts by sport governing bodies to prioritise research in this area will improve our understanding of the impairment-performance relationship, leading to better decision making and increased credibility in Para sport classification systems.